Ets1 and IL17RA cooperate to regulate autoimmune responses and skin immunity to Staphylococcus aureus - Battaglia, Michael; Sunshine, Alex C.; Luo, Wei; Jin, Richard; Stith, Alifa; Lindemann, Matt; Miller, Lloyd S.; Sinha, Satrajit; Wohlfert, Elizabeth; Garrett-Sinha, Lee Ann (Frontiers in Immunology, 2023)
Ets1 is a lymphoid-enriched transcription factor that regulates B and T cell functions in development and disease. Mice that lack Ets1 (Ets1 KO) develop spontaneous autoimmune disease with high levels of autoantibodies. Naïve CD4+ T cells isolated from Ets1 KO mice differentiate more readily to Th17 cells that secrete IL-17, a cytokine implicated in autoimmune disease pathogenesis. To determine if increased IL-17 production contributes to the development of autoimmunity in Ets1 KO mice, we crossed Ets1 KO mice to mice lacking the IL-17 receptor A subunit (IL17RA KO) to generate double knock out (DKO) mice. We found that the absence of IL17RA signaling did not prevent or ameliorate the autoimmune phenotype of Ets1 KO mice, but rather that DKO animals exhibited worse symptoms with striking increases in activated B cells and secreted autoantibodies. This was correlated with a prominent increase in the numbers of T follicular helper (Tfh) cells. In addition to the autoimmune phenotype, DKO mice also showed signs of immunodeficiency and developed spontaneous skin lesions colonized by Staphylococcus xylosus. When DKO mice were experimentally infected with S. aureus they were unable to clear the bacteria, suggesting a general immunodeficiency to Staphylococcal species. γδ T cells are important for control of skin Staphylococcal infections. We found that mice lacking Ets1 have a complete deficiency of the γδ T cell subset dendritic epidermal T cells (DETC), which are involved in skin wound healing responses, but normal numbers of other skin γδ T cells. To determine if loss of DETC combined with impaired IL-17 signaling might promote susceptibility to Staph infection, we depleted DETC from IL17RA KO mice and found that the combined loss of DETC and IL-17 signaling leads impairs clearance of the infection. Our studies suggest that defects in wound healing, such as that caused by loss of DETC, can cooperate with impaired IL-17 responses to lead to increased susceptibility to skin Staph infections.